Perceptions of 4-H alumni from four Ohio counties concerning the impact of 4-H on their career development - Janet Kingsbury Matulis (Ohio State University, 1984)
This study was to identify the perceptions of 4-H alumni from four Ohio counties concerning the impact of 4-H on their career development, as well as their current education/occupational and 4-H involvement characteristics. A researcher developed questionnaire was mailed to a stratified random sample. Alumni felt that 4-H had much impact on their self-awareness, particularly concerning positive interests and abilities. 4-H tended to have much impact upon the development of general work competencies reflecting humanizing skills and good work habits but had very little to do with the development of job-seeking skills related to interviews, applications and resumes. Alumni perceived 4-H as having great impact on general career awareness and less impact on more specific areas of career exploration and selection. However, county 4-H agents, 4-H leaders and other 4-H members were perceived as having very little impact on alumni career planning.
NAL abstract

Perceptions of 4-H alumni from four Ohio counties concerning the impact of 4-H on their career development - Janet Kingsbury Matulis; Lowell Hedges (1984)